Desempenho funcional de idosos com dor lombar: impacto de fatores clínicos, sociodemográficos, autopercepção e crenças - Flora Pereira Guerra (2013)
Musculoskeletal conditions in the elderly are an important cause of disability, especially for low back pain. Low back pain is a common condition among the elderly and there are evidences that those who have it report greater difficulty in performing activities of daily living. The objective of this study is to evaluate the relationship between functional performance of elders with low back pain and the following variables: sociodemographic and clinical factors, perceived health and beliefs about back pain. This is a cross-sectional study that used data from the Back Complaints in the Elders (BACE) international consortium. Information about sociodemographic factors (sex, age, marital status, formal education), clinical factors (intensity and frequency of pain, comorbidities), perceived health, beliefs about back pain and functional performance (measured by the disability component of the Late Life Function and Disability Instrument - LLFDI) were collected through self report. The sample consisted of 191 subjects above 60 years old with a new episode of back pain in at least six weeks who didnt have cognitive disorder, visual impairment and hearing and motor disabilities. A bivariate analysis was conducted between each independent variable and each outcome. Associations with p<0.20 were selected for the multiple linear regression analysis, that was carried out for each LLFDI domain. The multiple regressions coefficients of determination were significant despite the modest magnitude. The variables that were related to functional performance were beliefs about back pain, perceived health, formal education, pain frequency and marital status. The limitation dimension and the instrumental role domain showed the greatest coefficient of determination (R2=0,20) and both were related to beliefs and perceived health and frequency of pain was only related to the instrumental role. The results related to the management role domain didnt achieve statistical significance. These results may contribute to the improvement of health care professionals whose performance has been restricted to clinical aspects, also valuing the beliefs of elders and their self perceived health.